Effect of Andragogical Approach on the Academic Performance of Psychology Learners in Open University Malaysia (OUM) - Noor Hassline Mohamed (2013)
The study is attempts to investigate the effectiveness of andragogical approach employed by tutors on academic achievement of adult learners. The objective of the study is to measure if there are any significant differences in the learners ‘academic performances due to the individual capability in delivering the subject content. The study is analysed by an independent- samples t-test which conducted to compare learners score on the subject. This study initiated to compare the consequence of content delivery by two different background tutors. The samples chosen for this study are the second-year undergraduates for the subject Abnormal Psychology in Open University Malaysia (OUM). The sample size consisted of 48 learners who were randomly assigned to experimental group and control group, each consisting of 24 learners. The two tutors chosen for this study are, a tutor of andragogical approach (Tutor A) who completed the nine modules of Postgraduate Certificate in Open and Distance Learning (PGCert ODL) which involve a total of 400 learning hours preparing her for effective andragogical teaching skills for adult learners. The Tutor A is consigned as experimental group, while Tutor B is assigned to be in control group and was teaching the subject for the past 7 years without any certificate in teaching in open and distance learning skills. At the end of the semester, both groups were tested with a set of subjective tests to measure their understanding and knowledge of the subject. The findings showed that there was a significant difference in the scores for experimental group (M=57.17, SD= 14.12) and control group (37.92,SD=10.35), t (23)=9.25, p= 0.001.These results provided evidence that learners taught by andragogical approach consumed by Tutor A showed better score as compared to the control group. The vital outcome of the study is that a tutor with familiarity and trained in teaching in open and distance learning extent would be able to deliver the content effectively. It is proven that steps taken by OUM to progress internal academics had given a rewarding outcome in terms of learner’s academic achievement.